Dampak Hukum Pernikahan yang Tidak Tercatat (Nikah Siri) terhadap Status Anak dan Harta Bersama - I Putu kristiandi Saputra; Aturkian Laia (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Unregistered marriage remains a widespread practice in Indonesia. This research examines the legal impact of unregistered marriage on child status and joint property, as well as protection efforts through marriage validation (isbat nikah). Using a descriptive-analytical normative juridical approach, this research examines laws and regulations, Constitutional Court Decision No. 46/PUU-VIII/2010, and related academic studies. The findings show that children from unregistered marriages only have a civil relationship with the mother, limiting inheritance, support, and identity rights. Constitutional Court Decision No. 46/PUU-VIII/2010 provides a breakthrough by recognizing children's rights if biological ties can be proven, though implementation faces cultural barriers, social stigma, and complex evidentiary procedures. Joint property in unregistered marriages is not recognized by the state, causing wives to lose rights to matrimonial property and inheritance. Marriage validation serves as legal protection, yet not all applications are granted due to judicial considerations. This research recommends strengthening marriage registration socialization, improving access to marriage validation, and enhancing judges' capacity to understand the complexities of unregistered marriages.